Mit Rap zur Revolte: Die Bewegung Y’en a marre - Prause, Louisa (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
This study examines the successful mobilization of the movement Y’en a marre (We’re fed up) in Senegal in the run-up to the presidential elections in February and March 2012. The article traces this success back to the framing strategies applied by Y’en a marre and its creative use of resources. It is argued that an essential factor in the mobilization was the linkage established by the group between its protests against the third term bid of President Abdoulaye Wade and the precarious living conditions of Senegalese youth. Furthermore, Y’en a marre succeeded in presenting its protests as peaceful and constructive and thereby refuted common negative stereotypes of the youth and the Hip-Hop movement. By using the Hip-Hop movement and rap as resources to spread its message and mobilize new followers, Y’en a marre was able to compensate for its scarce financial resources.